Automatização de orçamento de projetos de redes de esgoto, abastecimento de água e de drenagem urbana - Soares, Everton Jhons Goes Silva (2024)
Cost prediction of a project is an indispensable tool for feasibility analysis, planning and management. The objective of this work is to develop and apply the Budget Module (UFC.Orca) to projects of water networks, drainage networks and sewage networks to obtain budgets for these disciplines. The computational tool has the capacity to automate the elaboration of costs based on the unitary cost base of the National System of Research of Costs and Indexes of Civil Construction (SINAPI) by writing it in a document. It is also intended to establish the average cost per meter of network, distribution of costs in stages and nature (labor, materials and equipment) for projects that share similar characteristics. The module was integrated into the UFC System software, capable of launching and dimensioning water supply systems, sewage collection and urban drainage works. The contribution of this work was the implementation of the detailing of costs by their nature and the parameterization of cost compositions to UFC.Orca. Regarding the application, study areas totaling 23 networks were taken, 8 sewage collectors, 7 rainwater collectors and 8 water distribution networks located in 9 municipalities in the State of Ceará. The module has successfully automated the budgeting process with minimal user intervention. The budgets generated used as reference the non- exempt cost tables of March 2024 from SINAPI and 028 from the Infrastructure Secretariat of the State of Ceará (SEINFRA).The results achieved include an average cost of R$ 293,97 per meter for sewage networks with manhole as structures, R$ 146,08 per meter for sewage networks using inspection and cleaning terminals instead of mentioned devices, R$ 395,02 permeter for drainage networks, and R$ 120,51 per meter for water distribution networks. It was found that the earthworks and pipe supply stages, as well as material costs, represented the greatest influence on the total direct cost of execution. The presets set for automatic generation were sufficient to model the situations present in the designs and provide the most appropriate compositions for preparing the budgets